Differential expression after UV-B radiation and characterization of chalcone synthase from the Patagonian hairgrass Deschampsia antarctica - Cuadra Burgueño, Pedro Osvaldo; Guajardo, Joselin; Carrasco-Orellana, Cristian; Stappung, Yazmina; Fajardo Morales, Victor Manuel; Herrera, Raul (My University, 2020)
Deschampsia antarctica inhabits the maritime territory of Antarctica and South Patagonia. It grows under very harsh environmental conditions. The survival of this species in low freezing temperatures and under high levels of UV-B radiation may constitute some of the most remarkable adaptive plant responses and suggests that this plant possesses genes associated with cold and UV tolerance. Frequently, increased levels of flavonoids have been linked to highly UV-B irradiated plants. Studies examining the biosynthesis of flavonoids in D. antarctica may provide clues to its success in this extreme environment. In this study, we characterized the family of genes encoding chalcone synthase, a key enzyme of the flavonoid biosynthetic pathway. DaCHS was cloned, sequenced and characterized by using software tools. CHS contains two domains, the N-terminal domain ranges from amino acid 8 to 231 and the C-terminal domain ranges from amino acid 241 to 391. Sequence analysis of the three family members revealed a high degree of identity after comparison with other monocotyledons such as Oryza sativa L., Zea mays L. and Hordeum vulgare L. According to these results, DaCHS can be grouped together with H. vulgare CHS1 in the same branch. The phylogenetic tree was built using MEGA software and the neighbour join method with 1000 bootstrap replicates. A model of DaCHS was constructed by way of structural tools and key amino acid residues were identified at the active motif site.
Keywords: deschampsia antarctica; poaceae; chalcone synthase gene; uv-b radiation; south patagonia; flavonoids